Low-temperature sol–gel oxide TFT with a fluoropolymer dielectric to enhance the effective mobility at low operation voltage. (9th May 2017) - Yu, Shang-Yu; Wang, Kuan-Hsun; Zan, Hsiao-Wen; Soppera, Olivier
Abstract: In this article, we propose a solution-processed high-performance amorphous indium–zinc oxide (a-IZO) thin-film transistor (TFT) gated with a fluoropolymer dielectric. Compared with a conventional IZO TFT with a silicon nitride dielectric, a fluoropolymer dielectric effectively reduces the operation voltage to less than 3 V and greatly increases the effective mobility 40-fold. We suggest that the dipole layer formed at the dielectric surface facilitates electron accumulation and induces the electric double-layer effect. The dipole-induced hysteresis effect is also investigated.